The Development of Indonesian Marriage Law in Contemporary Era - Mila Surahmi; Zaimah Husin; Nurifana Umar; Fatmawati; Tora Yuliana (Inovasi Pratama Internasional. Ltd, 2024)
Indonesia is a highly diverse country, comprising a multitude of tribes, groups, races, and religions, and is endowed with a rich cultural heritage. The heterogeneity of Indonesian society provides the context for interfaith and other forms of marriage. The specific legislation that governs marriage is Law Number 1 of 1974. It is commonly assumed that Law No. 1/1974 requires immediate revision due to its outdated nature and inability to address contemporary issues pertaining to marriage. Consequently, there are numerous provisions within the Marriage Law that require amendment or addition. For instance, there is a need to introduce more robust penalties for those who violate the Marriage Law, whether they are involved in interfaith marriages, same-sex marriages, polygamous marriages, or marriages contracted without the requisite formalities. This study aims to examine the evolution of marriage law in Indonesia and the challenges it has faced. It employs a descriptive qualitative approach with a literature review. The findings reveal that Indonesia's marriage regulation has undergone three distinct phases, each characterised by its own set of issues. Additionally, the country's marriage law has experienced two distinct periods: one following independence and the other following the enactment of Marriage Law Number 1 of 1974.